2021
DOI: 10.3389/fcvm.2021.619386
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol 4: The Notable Risk Factor of Coronary Artery Disease Development

Abstract: Background: Coronary artery disease (CAD) is the leading cause of death worldwide, which has a long asymptomatic period of atherosclerosis. Thus, it is crucial to develop efficient strategies or biomarkers to assess the risk of CAD in asymptomatic individuals.Methods: A total of 356 consecutive CAD patients and 164 non-CAD controls diagnosed using coronary angiography were recruited. Blood lipids, other baseline characteristics, and clinical information were investigated in this study. In addition, low-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…In the present study, we use six machine learning tools including KNN, LR, DT, SVM, MLP, and XGBoost-combined clinical features and blood lipid profile including sdLDL-C subfractions to predict CAD risk. We found that all models performed well in the prediction of CAD risk, which is consistent with a previous study that using above-mentioned models combing clinical data and sdLDL-C subfractions showed good performance for predicting CAD risk [ 3 ]. In addition, SVM, KNN, LR, and XGBoost models have also been reported to predict chronic kidney disease [ 67 ] and chronic obstructive pulmonary disease in Chinese population [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, we use six machine learning tools including KNN, LR, DT, SVM, MLP, and XGBoost-combined clinical features and blood lipid profile including sdLDL-C subfractions to predict CAD risk. We found that all models performed well in the prediction of CAD risk, which is consistent with a previous study that using above-mentioned models combing clinical data and sdLDL-C subfractions showed good performance for predicting CAD risk [ 3 ]. In addition, SVM, KNN, LR, and XGBoost models have also been reported to predict chronic kidney disease [ 67 ] and chronic obstructive pulmonary disease in Chinese population [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The inclusion criteria for participants were as follows: (i) CAD patients were diagnosed by coronary angiography, which is defined as coronary artery stenosis ≥50% in at least one main vessel or its major branches as described [ 29 ]; (ii) the non-CAD controls were diagnosed by coronary angiography without any luminal stenosis or plaque in main vessels and branches; (iii) the age of all participates >18 years. The exclusion criteria were as follows: (i) patients who had prior CAD or revascularization (percutaneous or surgical) [ 30 ]; (ii) participants who do not understand this research study [ 3 ]; (iii) participants who had severe medical disease, such as liver or kidney disease, thyroid disease, and malignant diseases [ 29 ], as well as immune-related sickness, nephropathic diseases, and respiratory diseases and also physiological conditions related to immune responses such as pregnancy [ 31 ]. The exclusion criteria for the non-CAD controls were the same as what mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recently performed study based on patients with coronary artery disease (CAD), compared to a control group, showed that triglycerides, LDL-C3, LDL-C4, LDL-C5, LDL-C6, and total LDL-C levels were significantly higher in patients with CAD, while LDL-C1 and HDL-C were significantly lower in the same group. The same review points out that lipid parameters associations with ischemic stroke in patients with non-valvular atrial fibrillation are still contradictory [ 19 ]. Therefore, we agree that sampling LDL-C subfractions on larger populational groups would help create better prediction scores for major CV events in the general population.…”
Section: Discussionmentioning
confidence: 99%